Accumulation, decumulation and stability trends of avian malaria parasites and their effects on individual blue tits (Cyanistes caeruleus) - Wright,Lillian (2025)
Global rising temperatures is impacting species interactions worldwide including those between host and parasites. A long-term study on a population of blue tits (Cyanistes caeruleus) linked increases in avian malaria parasites to rising temperatures. Understanding the consequences that these increases in avian malaria parasites are causing is vital. Therefore, data from the past 28 years on this population of blue tits was used to understand the effects that these climate driven increases in malaria parasite prevalences have on individual hosts. The purpose of this study was to look at accumulation, decumulation and stability trends of avian malaria parasites for infected and co-infected individuals, some of which included recaptured individuals. Furthermore, this study also aimed to analyze the effects of Haemoproteus, Plasmodium and Leucocytozoon infections on the breeding performance and morphometric measurement of individual blue tits. These aims were achieved through utilizing blood samples, breeding records and morphometric measurements taken from the population between 1996 to 2024. DNA extractions from the blood samples were analyzed using a PCR analysis to identify the parasite genera present. The results showed that some of these infections are chronic and can last multiple years. Furthermore, facilitation of Leucocytozoon was found in individuals that were previously infected with Haemoproteus. Some negative fitness effects were observed in infected individuals, including reduction in brood size and reduced nestling survival for females with either Plasmodium or Leucocytozoon infections. Furthermore, uninfected females had a larger mass than those with a single infection, while nestling survival (clutch-brood) was higher in females with a single infection compared to females with triple infections. Overall, although this population is showing an increase in parasite prevalences, the negative effects on fitness are not leading to an overall population decrease. As this study only looked at parasite presence, the levels of parasitemia along with the effects that infected parents have on nestlings would provide valuable insight as to the long-term consequences of these parasites and how this may change with further increases in temperature.